ЗНАЧЕНИЕ ЦИФРОВИЗАЦИИ ДОШКОЛЬНОГО ОБРАЗОВАНИЯ В СОВРЕМЕННОМ ОБЩЕСТВЕ - Ким И.Н. (Лучшие интеллектуальные исследования, 2023)
Abstract: The article discusses the features and possibilities of digitalization in the field of preschool education.